2010
DOI: 10.1007/s00339-010-5642-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive investigation of art paintings by terahertz imaging

Abstract: International audienceTerahertz electromagnetic waves propose attractive features such as non-invasive and non-destructive analysis, transparency and good penetration depth through various materials, low scattering and broad spectral bandwidth. In this paper, we demonstrate the capability of terahertz imaging for the investigation of art paintings. The imaging system is able to reveal buried layer information such as a graphite handmade sketch covered by several layers of painting. In addition, taking advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 23 publications
0
47
0
3
Order By: Relevance
“…In this field of art conservation, terahertz (THz) imaging techniques have already been applied for the analysis of artworks such as fresco [1,2], canvas paintings [3,4], and old parchments [5]. However, very few studies can be found on THz imaging in anthropology and paleontology [6] but this spectral range can offer unique advantages compared to the x-ray gold standard, which is not recommended owing to the fragility/uniqueness of the samples and the problem of sample radiometric dating after x-ray irradiation [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this field of art conservation, terahertz (THz) imaging techniques have already been applied for the analysis of artworks such as fresco [1,2], canvas paintings [3,4], and old parchments [5]. However, very few studies can be found on THz imaging in anthropology and paleontology [6] but this spectral range can offer unique advantages compared to the x-ray gold standard, which is not recommended owing to the fragility/uniqueness of the samples and the problem of sample radiometric dating after x-ray irradiation [7].…”
Section: Introductionmentioning
confidence: 99%
“…First, we were interested in comparing the CW imaging system with a homemade pulsed THz imaging system based on a femtosecond laser and a time-domain spectrometer [19,20]. For this purpose, we used another Gunn diode source to pump a frequency tripler in order to deliver 0.2 mW at 240 GHz.…”
Section: Cw Imaging Of Painting Artworkmentioning
confidence: 99%
“…The recently introduced terahertz (THz) imaging technique overcomes this obstacle by yielding a 3D structure. Being a complementary technique to XRR and IR, in terms of pigment identification, THz imaging also allows the collection of data on the thickness of various pictorial layers [8,9]. Another important method for the study of hidden paintings is neutron activation autoradiography (NAAR), which allows the identification of a wide range of pigments [10].…”
Section: Introductionmentioning
confidence: 99%